Terpenoids and phenolics from Plectranthus strigosus, bioactivity screening - Gaspar-Marques, Cristina (2015)
Further studies on Plectranthus sp. (Lamiaceae) led to the isolation of terpenes and phenol esters from Plectranthus strigosus Benth. ent-16-Kauren-19-ol (1), ent-16-kauren-19-oic acid (2), xylopic acid (3), xylopinic acid (4), hinokiol (5), 4 beta,6 beta-dihydroxy-1 alpha,5 beta(H)-guai-9-ene (6) 4 beta,6 beta-dihydroxy-1 alpha,5 beta(H)-guai-10(14)-ene (7), mixtures of hexacosan-1,26-diol and octacosan-1,28-diol ferulate diesters (8), of esters from ferulic acid and fatty alcohols (9) and of esters from fatty acids and 2-(4-hydroxyphenyl)-ethanol (10) were for the first time isolated from this genus. Supplementary spectral data for 3,8 and parvifloron D (11) metabolites are also presented. A bioactivity study revealed herpetic inhibitory properties for (1) and (2), and antioxidant ability for (5) and (8) phenolic constituents.